Clinical prognostic significance of regional and extended lymphadenectomy for biliary cancer with para-aortic lymph node metastasis: A systematic review and meta-analysis. Issue 7 (July 2016) - Gu, Jinyang; Xia, Lei; Xu, Biyun; Lu, Tianfei; Halmurat, Obulkasim; Wang, Jun; Zhang, Jianjun; Ding, Yitao; Xia, Qiang
Abstract: Background: The aim of our study was to evaluate clinical prognostic significance of regional and extended lymphadenectomy for biliary cancer with para-aortic lymph node metastasis. Methods: A thorough literature search was performed in PubMed/Medline, Cochrane Central Register, Embase, ISI Web of Science and Google Scholar between January 1965 and May 2014 with restricted articles for the English language. Data were processed for a meta-analysis by RevMan 5 software. Results: Altogether 10 retrospective studies were finally enrolled in our study. For positive para-aortic lymph node group irrespective of regional lymph node metastasis, the overall 1-, 3-, 5-yr pooled RR estimates of survival rates were 2.30, 1.70, and 1.42. There were significant differences between positive para-aortic lymph node group and negative group. For positive para-aortic lymph node group in the setting of regional lymph node metastasis, the overall 1-, 3-, 5-yr pooled RR estimates of survival rates were 1.57, 1.29, and 1.11, respectively. The long-term outcomes referred to 5-yr survival rate were similar between para-aortic lymph node metastasis and regional lymph node metastasis only. Discussion: Radical resection with extended lymphadenectomy should be caution in terms of the results of an intraoperative sampling biopsy of para-aortic lymph node, which requires a well-designed, prospective controlled study in the future.